Rethink about electrolyte: Potassium fluoride as a promising additive to an electrolyte for the water oxidation by a nanolayered Mn oxide - Najafpour, Mohammad Mandi; Ghobadi, Mohadeseh Zarei; Hosseini, Seyedeh Maedeh; Chae, Keun Hwa; Mehrabani, Somayeh; Rafighi, Panin; Bagheri, Robabeh; Song, Zhenlun (PERGAMON-ELSEVIER SCIENCE LTD, 2017)
Water oxidation is a bottleneck of the hydrogen production through the water-splitting reaction. Herein, the promising role of fluoride on the water-oxidizing activity of a nano layered Mn oxide under the electrochemical condition is reported. The experiments show the increase of the water-oxidizing activity of the nanolayered Mn oxide under an electro-water oxidation circumstance in the presence of potassium fluoride as a promising additive to an electrolyte. As a result, the required overpotential is decreased and the yield of oxygen evolution raised in the water-oxidation reaction. (C) 2017 Hydrogen Energy Publications LLC. Published by Elsevier Ltd. All rights reserved.